2004
DOI: 10.1111/j.1399-6576.2004.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Dixyrazine for the prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy

Abstract: Prophylactic dixyrazine is an effective, safe, and cheap antiemetic drug for laparoscopic cholecystectomy without involving any significant adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Additionally, in patients given gabapentin, fentanyl requirements were reduced, which is consistent with the previously reported opioid‐sparing effects of this treatment 75 . The efficacy of dixyrazine, a phenothiazine derivative, was studied by Glaser et al 76 . in a trial of 197 patients.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Additionally, in patients given gabapentin, fentanyl requirements were reduced, which is consistent with the previously reported opioid‐sparing effects of this treatment 75 . The efficacy of dixyrazine, a phenothiazine derivative, was studied by Glaser et al 76 . in a trial of 197 patients.…”
Section: Resultssupporting
confidence: 80%
“…Eight studies 7,70–76 evaluated the efficacy of different anti‐emetic regimens in patients undergoing LC. Two placebo‐controlled trials 7,73 showed serotonergic antagonists such as ondansetron to be effective in reducing postoperative nausea 7 and vomiting 7,73 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing laparoscopic cholecystectomy are especially prone to PONV, with a reported incidence of 53%-72% [20,22,23,25]. In various attempts to decrease this high incidence, numerous antiemetics have been studied [9,10,22]. However, because of the multifactorial origin of PONV, none of the currently available antiemetics is fully effective in all patients.…”
mentioning
confidence: 98%
“…13,35,37,39 One new RCT indicates that dixrazine is effective in the prophylaxis of postoperative nausea when compared with placebo (Category A3-B evidence), with equivocal findings reported for postoperative vomiting, headache, dizziness, and anxiety (Category A3-E evidence). 40 New literature is insufficient to further evaluate postoperative nausea and vomiting findings, as reported in the original Guidelines, for the following drugs: hydroxizine (Category A3-B evidence), perphenazine (Category A3-B evidence), and prochlorperazine (Category…”
Section: 33mentioning
confidence: 99%